Synergistic Probiotic–Postbiotic Therapy Ameliorates Hyperuricemia via Multi-Target Regulation of Purine Metabolism and Gut Microbiota - Lu Ren; Shiting Liu; Shangshang Wang; Zhenrui Li; Fuping Lu; Xuegang Luo (Foods)
Hyperuricemia (HUA), a metabolic disorder characterized by elevated serum uric acid (UA) levels, often leads to renal and hepatic complications. This study evaluated the synergistic effects of Pediococcus acidilactici GQ01, a probiotic strain isolated from naturally fermented wolfberry, in combination with a complex (T) composed of buckwheat-fermented postbiotics, collagen peptide and multiple medicinal food blends in a murine HUA model. The combination therapy (T + GQ01) not only significantly reduced serum UA levels more effectively than T or GQ01 alone but also demonstrated superior inhibition of XOD activity and enhanced ADA activity, both of which are key regulators of purine metabolism. Additionally, T + GQ01 ameliorated kidney injury, as evidenced by reduced serum CRE and BUN levels, and improved liver function, indicated by decreased ALT and AST activities. Histopathological analysis further confirmed the protective effects of T + GQ01 on renal and hepatic tissues. Moreover, T + GQ01 modulated intestinal flora composition, promoted beneficial genera such as Weissella and Bacteroides, and enhanced the production of SCFAs, particularly propionic and butyric acids, which play critical roles in maintaining intestinal health. These findings suggest that the cocktail-like microecological regulator combining P. acidilactici GQ01, buckwheat-fermented postbiotics, collagen peptide and multiple medicinal food blends represents a promising therapeutic strategy for HUA by targeting multiple metabolic pathways, underscoring its potential as a novel intervention for HUA and its complications.